Tuning of defects induced visible photoluminescence by swift heavy ion irradiation and thermal annealing in zinc oxide films. (June 2021) - Singh, R.G.; Gupta, Himanshi; Mehra, R.M.; Singh, Fouran
Abstract: Present study reports the influence of electronic energy deposition on sol-gel grown zinc oxide thin films with different type of microstructures for tailoring the defects induced photoluminescence properties. The microstructure of the films was modified by the controlled thermal annealing and the nature of defects were tuned by swift heavy ions (SHI) irradiations at varying ion fluences of such thin films. It is observed that all the films show two emission bands in the spectral range of 350 nm–1000 nm; (i) a very weak UV-emission band and (ii) a broad visible emission band. The UV-emission band is attributed to the band to band transition while the visible emission to the deep-level defects. The maximum visible emission lies in the green emission region which enhanced with increasing annealing temperature for the samples annealed in controlled Argon gas environment in comparison of samples annealed in an oxygen environment. The intensity of the visible emission band was found to be increased with ion irradiation at low ion fluences while showing reduction at higher ion fluences along with peak broadening. The films annealed at higher annealing temperature exhibit shifting of peak maximum from green region to red region at higher fluences. The peak shifting and peak broadening at higher ion fluences could be attributed to the formation of the high density of complex defects such vacancies cluster and ionized oxygen vacancies in the lattice as tuned under the influence of electronic energy deposition through SHI irradiations. Thus, it is suggested that the intense luminescence induced by the defects could be tuned in controlled manner by selecting the proper irradiations parameters and thus it would be very interesting for the development of the optoelectronic applications. Highlights: Tuning of defects related photoluminescence by ion irradiation. Visible PL emission as a function of microstructure and irradiation parameters. Formation of vacancies cluster and ionized oxygen vacancies by ion irradiation.